Rapid detection of earthquake damage areas using VIIRS nearly constant contrast night-time light data. Issue 5 (19th March 2019) - Fan, Xiwei; Nie, Gaozhong; Deng, Yan; An, Jiwen; Zhou, Junxue; Li, Huayue
ABSTRACT: To rapidly identify earthquake damage areas after earthquakes occur, a method based on Visible Infrared Imaging Radiometer Suite (VIIRS) night-time light (NTL) images with nearly constant contrast (NCC) is proposed. The differences between post-earthquake and mean image of 3 months VIIRS NCC NTL before an earthquake are taken to reflect the effects of earthquakes on city light brightness loss, with eliminating the influence of clouds, lunar and solar irradiance, and poor-quality NCC NTL pixels. In addition, the standard deviation (STD) of the NTL images collected during the 3 months before an earthquake is calculated. Then, the areas with the differences less than −1 times the local STD are taken to be earthquake damage areas, and the areas with differences less than −2 times the local STD are taken to be severely damage areas. Finally, this method is applied to the 2015 Nepal moment magnitude (Mw) 7.8 earthquake, the 2014 Chile Mw 8.1 earthquake, and the 2015 Chile Mw 8.3 earthquake. Compared with Prompt Assessment of Global Earthquakes for Response output for selected cities impacted by these earthquakes, the results show that the overall accuracies are 14.9%, 75.0%, and 68.4% respectively, for the three earthquakes with the accuracy increases with greater earthquake intensities.